Peculiarities of law enforcement system functioning in the context of digitalization - Popovich, Iryna; Rusetskyi, Anatolii; Nazymko, Ehor; Korniienko, Maksym; Polianskyi, Anton (Edelweiss Applied Science and Technology, 2024)
The relevance of the topic under study in this article is due to the fact that for the purpose of balanced and sustainable development of society, the law enforcement system must also adapt to the conditions of digitalization. This should be done by maximizing the introduction of advanced digital technologies, including artificial intelligence, into the daily activities of law enforcement agencies. It is noted that the processes of digitalization have accelerated significantly in the context of the coronavirus pandemic, which has led to the introduction of a wide range of restrictions, in particular, quarantine, curfews, restrictions on business and public authorities in the provision of public services, the mechanisms for the implementation of which have emerged in the light of digital technologies. The authors analyzed the essence of the functioning of the law enforcement system in conditions of digitalization, such as: development of the family institution; aggravation of the problem of preventing and countering domestic violence in the conditions of martial law; rethinking the meaning of pretrial investigation and criminal intelligence (analysis) in the context of crime transformation. Peculiarities of digitization of modern anti-corruption tools, the fundamental importance of international partnership in the field of law enforcement in the conditions of digitalization are also considered.